Empowering Vocational Informatics Students with Android-Based Problem-Based Learning Media - Khakim, Muhamad Lutfi; Nidhom, Ahmad Mursyidun (Universitas Negeri Malang, 2024)
Technology is experiencing rapid development and is in line with the increasing need for adequate human resources (HR). There is a need for educators to prepare themselves to teach and produce high-quality individuals. However, many students are still not ready to enter the workforce. To prepare high-quality students, a good conceptual understanding is needed, and to achieve this, students must have strong learning motivation. One way to increase motivation is by using the Problem-Based Learning model and supported by Android-based learning media. The purpose of this research and development is to (1) Develop, (2) Test the feasibility, and (3) Determine the increase in student motivation in using Android-based learning media with a Problem-Based Learning model in Informatics subjects at vocational high schools that have been developed. The 4D model was chosen for this development, with stages including define, design, develop, and disseminate. The development result is an Android-based learning media called